2008
DOI: 10.1159/000142612
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Shift of Transforming Growth Factor-Beta-1 from Inhibition to Stimulation of Vascular Smooth Muscle Cell Growth Is Based on Unconventional Regulation of Proliferation, Apoptosis and Contact Inhibition

Abstract: Background: TGF-β shifts from inhibition to stimulation of vascular smooth muscle cell (vSMC) growth when cell density increases. How proliferation and apoptosis contribute to this shift is still unknown. Methods: In sparse and confluent V8 vSMC treated or not with TGF-β1 (1 ng/ml) for 3 days, cell number, mitotic activity, cell-cycle-regulatory protein levels, caspase-3 and phosphoinositide 3-kinase (PI3-K) activities were studied. Results: In TGF-β1-treated cells, (i) the growth curve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…2I and J). It has generally been suggested that contact inhibition of cell proliferation occurs when a cell culture reaches confluence (Hneino et al, 2009). However, the proliferation of SMCs was significantly inhibited in the micropillar substrates even though the cells did not reach the confluent state (compare Fig.…”
Section: Resultsmentioning
confidence: 92%
“…2I and J). It has generally been suggested that contact inhibition of cell proliferation occurs when a cell culture reaches confluence (Hneino et al, 2009). However, the proliferation of SMCs was significantly inhibited in the micropillar substrates even though the cells did not reach the confluent state (compare Fig.…”
Section: Resultsmentioning
confidence: 92%
“…In VSMCs, TGF-␤ has historically been considered antiproliferative (2, 14 -16); however, other findings suggest that TGF-␤ and its downstream Smads stimulate growth in primary VSMCs (9,18,19,(25)(26)(27). Adding to this uncertainty, in cultured cells TGF-␤1 is suggested to switch between growth stimulation and growth suppression depending on concentration (3,18) and cell density (9). This pleiotropic and often discordant nature of TGF-␤/Smad signaling and its control of tissue growth demand clarity.…”
Section: With the Use Of Commercial And Primary Preparations Along Wimentioning
confidence: 99%
“…TGF-b controls VSMC proliferation (Hneino et al 2008). Altered VSMC proliferation by abrogation of TGF-b signaling could take part in the anomalies of Sections from the descending aorta stained with a-SMA from E14.5 (a, b), E15.5 (c, d), E17.5 (e, f), E18.5 (g, h) embryos.…”
Section: Expression Pattern Of Tbriimentioning
confidence: 99%